Astaxanthin alleviates oxidative damage in acute pancreatitis via direct antioxidant mechanisms - Özbeyli, Dilek; Gürler, Esra Bihter; Buzcu, Hülya; Çilingir-Kaya, Özlem Tuğçe; Çam, Muhammet Emin; Yüksel, Meral (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Astaxanthin (ATX) is a naturally occurring carotenoid and a potent antioxidant. Various anti-inflammatory effects of ATX have been examined. We aimed to investigate the protective effect of ATX and its mechanism in a cerulein-induced acute pancreatitis rat model.Materials and Methods: The rats were randomized into 2 main groups as control (C) and acute pancreatitis group (AP). AP group was subsequently divided into subgroups as AP+vehicle (AP), AP+ATX, and ATX+peroxisome proliferator-activated receptor-alpha antagonist GW6471 (ATX+GW) groups. To induce AP, the rats were administered cerulein (50 µg/kg, intraperitonally [ip]) at 1 hour intervals, whereas the C group received saline. The AP group was treated with vehicle olive oil, ATX 40 mg/kg/orally, or GW6471 and ATX (GW1 mg/kg/ip; ATX; 40 mg/kg/peroral). Treatments were administered after the 1st cerulein injection. At the 7th hour after the final injection, the rats were killed and the pancreatic tissue was used for the determination of malondialdehyde (MDA), glutathione (GSH), and myeloperoxidase (MPO) activities and luminol-lucigenin chemiluminescence levels. Serum amylase, lipase, and histopathological analyses were performed.Results: Elevated serum lipase and amylase levels in the vehicle-treated AP group (p<0.01) decreased in the ATX and ATX+GW groups (p<0.05). In the AP groups, GSH was reduced and MDA, MPO, luminol, and lucigenin levels were increased (p<0.05-0.001). ATX reversed these changes (p<0.05-0.001). The vehicle-treated group revealed significant severe cytoplasmic degeneration and vacuolization, whereas ATX ameliorated these destructions. GW6471 did not abolish the positive effects of ATX biochemically or histologically.Conclusion: ATX has a potent protective effect on AP via its radical scavenging and antioxidant properties. Therefore, we believe that ATX may have therapeutic potential.